Pandangan Hukum Islam terhadap Status Muflis (Debitur Pailit) sebagai Gharimin (Mustahik Zakat) - Desi Ratnasari; Muhammad Iqbal Fasa; A. Kumedi Ja’far (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The development of sharia economy in Indonesia is increasing. Islamic economic development can be seen from the development of Islamic financial institutions and the Islamic financial instruments they offer, ranging from Islamic banks, Islamic capital markets, and Islamic insurance. With these developments, nowadays financing activities with sharia contracts are increasing and growing rapidly. However, only a few can pay it off. In other words, non-performing financing or bad loans at Islamic financial institutions often occur. Non-performing financing caused by the inability of the customer as a debtor to pay debts to a financial institution as a creditor resulted in the customer being bankrupted by the financial institution as a creditor. Bankruptcy is defined as the inability of the debtor or debtor (can be a person, legal entity, company) which is proven based on a court decision that the debtor has stopped paying his debts (unable to pay off debts) which results in general confiscation of his assets, so that the debtor is no longer entitled to manage his assets. . If it is associated with zakat, one of the ashnaf of zakat is gharimin or people who are in debt. Zakat institutions in Indonesia have not made bankrupt customers as gharimin who are entitled to receive zakat. The formulation of the problem in this paper is to find out the views of Islamic law on the status of bankrupt debtors as gharimin. The conclusion is that the status of a bankrupt debtor can be determined as a gharimin who is entitled to receive zakat. The use of debt in question can be for personal or public interest. The distribution pattern can use the qardh hasan pattern where the zakat given to the gharimin is not to be owned but to be returned again. The zakat funds are not only used to pay off debts, they can also be used as initial capital for bankrupt debtors to restart their business. Keywords: bankrupt debtor, gharimin, zakat mustahik.